Educational Self-Esteem Research Over the Last 50 Years: A Bibliometric Analysis of the Scopus Database - Hanif Alyaa Nabilla; Djamilah Bondan Widjajanti; Raden Rosnawati (Journal of General Education and Humanities, 2025)
This study aims to analyse research trends on children's self-esteem education. This study uses the keywords "self-esteem" and "education" in the Scopus database, using the PRISMA framework and obtaining 772 documents analysed using VOSviewer, Biblioshiny, Microsoft Excel, and Publish or Perish (PoP) to map the results of the analysis with bibliometrics. The analysis results show that research on educational self-esteem from 1975 to 2025 experienced a peak in publication in 2024 and a productive peak in 2014 with an h-index of 16. The last 5 years of research on self-esteem are associated with children's social and psychological dimensions and academic performance. From the results of the systematic literature review, it is known that self-esteem affects children's confidence in their abilities, and this affects children's academic performance at school. Thus, learning that can improve students' self-esteem is supportive, reflective, participatory, problem-solving, and communicative learning, because these five characteristics help students feel valued.